Plan de marketing para la empresa Autocofic Import S.A. comercializadora de repuestos automotrices de la ciudad de Quito - Asimbaya Simbaña, Claudia Soraya (2015)
The overall objective of this research was to conduct a marketing plan for the company Autocofic Import SA distributor of automotive parts, which maximizes profits. Achieved through the use of deductive, inductive and descriptive methods that allowed validate data obtained in the field study and then proceed to generalize to more broader theoretical positions, as well as general knowledge contrast with these results and the use of technical research and survey. A situational analysis of the company Autocofic Import SA, where an external analysis of the political, economic, social, technological, cultural, subsequent factors to this we proceeded to capture the personal analysis of the five forces of Porter took place took place, is structured EFE matrix which yields a 1.88 weighted results showing that there is less threat that must be controlled, just as the internal analysis where the history of the company under study is performed studies, surveys applies to customers and interpreted its results, this allowed us to build the EFI 2.31donde matrix which results we find that the company has the opportunity to allow yourself a positive position against the competition. Finally, the conclusions that have been reached after the completion of this work, where it is described as one of the most important ones are: that with the implementation of the proposed marketing plan will help to achieve greater effectiveness and competitiveness Marketing management, environment recommendations also raises the final analysis presented, are waiting to be considered by the directors of the Company